Innovative moments on online Cognitive Behavioral Therapy for alcohol dependence: a case study - Leon Ferreira, Maira (2022)
Online Cognitive Behavioural Therapy (CBT) is a promising intervention for reducing alcohol consumption among the population. However, due to the lack of studies in the area, the present study aims to evaluate the effects of the therapeutic process of online CBT for alcohol addicts in a Brazilian sample. Thirty-six recordings of six male participants diagnosed with alcohol dependence, who sought treatment to cease or reduce the substance’s consumption, were analysed using the Innovative Moments Coding System (IMCS). The IMCS is a method that analyses changes occurred during the therapeutic process. The results suggested: (1) an increase in the number of Innovative Moments (IMs) from the beginning to the end of the sessions in all analysed cases, and (2) a correlation between a decrease in the doses of alcohol consumption at the end of the sessions and the increase of IMs. The present study successfully applies for the first time the IMCS in alcohol dependence and proved to be an adequate method to evaluate the online therapy process for this sample. However, it is necessary to conduct further research to confirm the IMCS’s effectiveness for alcohol dependence.